Dr. Tino Ferrari — Deep Plane Facelift - Ferrari, Tino (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Tino Ferrari. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003248; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS